Sweden and the problem of coherence of the Baltic Europe states’ cooperation in 2018 - Kubka, Andrzej (Wydawnictwo Uniwersytetu Gdańskiego, 2018)
Holding the presidency in crucial regional organizations and formats in Baltic Europe in 2018 (Nordic Council of Ministers, Council of the Baltic Sea States, Barents Euro-Arctic Council, formats N5 and NB8) Sweden is in exceptional position to enhance this region’s coherence. The goal of the analysis in the article is to explain in what way Sweden aims to coordinate the regional policy agenda. Official programmatic documents give the ground to assume that Sweden is seeking to achieve a regional coordinator’s role and is actively realizing planes which promote regional coherence in Baltic Europe. At the same time Sweden takes into consideration the European and global contexts of the policies in this region. The main overarching field of engagement in this respect becomes the realization of the UN Agenda 2030. The characteristics, i.e. scope and elaboration, of the political programmes of the Swedish presidency in the mentioned above organizations and formats suggests that Nordic as well as Nordic-Baltic cooperation are considered as the most important ones. Celem analizy podejmowanej w artykule jest wyjaśnienie, jakie działania planuje podjąć Szwecja jako podmiot polityki zagranicznej na regionalnej arenie Europy Bałtyckiej w 2018 roku i w jakiej mierze mogą się one odnosić do zagadnienia budowania spójności tego regionu. Wyjątkowość pozycji Szwecji w tym okresie wynika ze sprawowania jednocześnie funkcji przewodnictwa w kilku organizacjach i formatach współpracy regionalnej (Nordyckiej Radzie Ministrów, Radzie Państw Morza Bałtyckiego, Radzie Euro-Arktycznego Regionu Morza Barentsa, formatach N5 i NB8). Na podstawie analizy dokumentów programowych i działań podejmowanych w pierwszej połowie 2018 roku można stwierdzić, że Szwecja stara się przyjąć rolę koordynatora regionalnego i aktywnie realizuje plany sprzyjające budowaniu spójności regionu Europy Bałtyckiej, nie tracąc z pola uwagi powiązań problematyki regionalnej z polityką europejską i polityką w skali globalnej. Podstawową przedmiotową płaszczyzną tego ...